The Platelet Aggregation Score and Its Correlation to β- Thromboglobulin and Platelet Factor 4 Levels - Kaplan, Svetlana; Kaplan, Alexander; Marcoe, Karen F.; Gey, Gerge O.; Schiller, Harvey; Roby, Paul V.; Fisher, Llod D.; El-Massry, Sherif; Sauvage, Lester R. (Clinical and applied thrombosis/hemostasis, 1995)
We describe a new method of interpreting platelet aggregometry results and its correlation to platelet secretory protein levels. We studied 123 healthy male volunteers, 37-85 years of age. The aggregation response to 2.5 μM ADP was measured in a standardized platelet suspension (SPS) prepared from platelet-rich plasma. Turbidimetic measurements included amplitude of the primary aggregation wave (Amp1), maximum aggregation amplitude (Amax), and area under the aggregation curve (Sagg). A platelet aggregation (PA) score was calculated as (Amp 1 /A max) ·Sagg ·(whole-blood platelet count/SPS platelet count). β-Thromboglobulin (β-TG)and . platelet factor 4 (PF4) levels were measured by radioimmunoassay. The PA score correlated significantly (p < 0.0001) with β-TG (r = 0.86) and PF4 (r = 0.87). It was concluded that the PA score correlates closely with individual subjects' propensities to platelet activation, as reflected by plasma β-TG and PF4 levels. Key Words: Platelets-Platelet aggregometry-Platelet secretory proteins.